Stopping in (e)motion: Reactive action inhibition when facing valence-independent emotional stimuli - Battaglia, Simone; Cardellicchio, Pasquale; Di Fazio, Chiara; Nazzi, Claudio; Fracasso, Alessio; Borgomaneri, Sara (Frontiers in Behavioral Neuroscience, 2022)
Emotions are able to impact our ability to control our behaviors. However, it is not clear whether emotions play a detrimental or an advantageous effect on action control and whether the valence of the emotional stimuli affects such motor abilities. One way to measure inhibitory control is the stop-signal task (SST), which estimates the ability to cancel outright an action to the presentation of a stop signal by means of the stop signal reaction times (SSRT). Impaired as well as facilitated action control has been found when faced with emotional stimuli as stop signals in SSTs and mixed results were observed for positive versus negative stimuli. Here, we aimed at deeper investigate these unsolved issues. Action control capabilities were tested in 60 participants by means of a Stop Signal Task, in which the stop signals were represented by a fearful and a happy body posture together with their neutral counterparts. Results showed that both positive and negative body postures enhanced the ability to suppress an ongoing action compared to neutral body postures. These results demonstrate that emotional valence-independent emotional stimuli facilitate action control and suggest that emotional stimuli may trigger enhanced sensory representation and/or attentional processing that may have facilitated stop-signal and hence improved inhibitory performance.